2005
DOI: 10.1185/030079905x48438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nilvadipine and amlodipine in patients with mild to moderate essential hypertension: a double blind, prospective, randomised clinical trial

Abstract: Nilvadipine or amlodipine produced comparable effects on DBP and shared a similar adverse effect profile. A favourable effect on lipid profile was observed following nilvadipine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Participants were randomized (1:1) to a daily dose of 8 mg of nilvadipine or placebo. It was previously shown that properties of 8 mg of nilvadipine are comparable to 5 mg of amlodipine [24] . In the Nilvad trial, the intervention resulted in a reduction of BP of 7.5/3.0 mmHg compared to placebo [25] .…”
Section: Methodsmentioning
confidence: 97%
“…Participants were randomized (1:1) to a daily dose of 8 mg of nilvadipine or placebo. It was previously shown that properties of 8 mg of nilvadipine are comparable to 5 mg of amlodipine [24] . In the Nilvad trial, the intervention resulted in a reduction of BP of 7.5/3.0 mmHg compared to placebo [25] .…”
Section: Methodsmentioning
confidence: 97%
“…Nilvadipine is currently licensed as an antihypertensive agent and has a better tolerability profile than nitrendipine, amlodipine or nifedipine, despite similar efficacy for reducing BP in hypertensive individuals (Faust, 1992;Keck, 1992;Leonetti, 2005). However, the treatment of normotensive individuals with nilvadipine might cause an undesired reduction in BP and/or orthostatic hypotension (OH), particularly in AD patients many of whom have impaired cerebrovascular responses and are already prone to hypotension (Allan et al, 2007;Schuff et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Accumulating evidence indicates that specific classes of antihypertensive agents may exhibit a wide range of effects on lipid metabolism beyond their BP-lowering effect [17,18]: while some exert beneficial or neutral effects on lipid profiles, others adversely affect it [17,18]. Accordingly, previous studies have demonstrated that the long-acting dihydropyridine calcium channelblockers (CCBs), particularly amlodipine (AML), exert beneficial effects on lipid profiles through their anti-atherogenic, anti-oxidant, anti-inflammatory and anti-proliferative effects as well as potentiation of nitric oxide activity [17,18,19,20,21]. On the other hand, thiazides, such as hydrochlorothiazide (HCZ), have been reported to negatively affect lipid status [18,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%